Table of Content - - (Journal of natural sciences, life and applied sciences, 2024)
Table of Content 1. Necessary measures to prevent the risk of flooding in urban centers in the Wadi Inawen basin in Morocco: Applied study Dr. Ali Neddama, Dr. Jaouad El-Bazoui, Dr. Abdelouahed Bouberria 2. Morphometric and hydrological characteristics of Abo-Habil Basin, western Sudan Co-Prof. Ummhani Idris Ahmed